Tracheal Chondrosarcoma: Systematic Review of Tumor Characteristics, Diagnosis, and Treatment Outcomes with Case Report - Emily A. Kutzner; Joshua S. Park; Salman Zaheer; Jared C. Inman (Case Reports in Oncological Medicine)
To our knowledge this is the first systematic review of tracheal chondrosarcoma treatment outcomes. Management insights are thoroughly discussed. Men constitute 93.8% of cases, and most of these occur in the distal trachea. The most common symptom, dyspnea, occurs in virtually all patients. Extratracheal extension had occurred in 78.6% of patients. Definitive treatment with tracheal resection showed no recurrences in 10 patients with mean follow-up of 3.1 years. Adjuvant radiotherapy may be utilized for improving local control when open complete resection cannot be performed, but only after endoscopic excision of gross tumor.